Assessing Knowledge Transformation Through an Authentic Assessment Ecosystem: Evidence from a First-Cycle Classroom Action Research Study in an Introductory Economics Course - Raymond Allan G. Vergara; Kimberly Christie S. Vergara (Future Science / FSH-PH Publications, 2026)
This first-cycle classroom action research study examines whether students’ perception of their economic knowledge and skills can transform through an authentic assessment ecosystem of an introductory economic course. The authentic assessment ecosystem comprised learning circles organized around real Philippine economic issues, weekly scaffolded individual assignments grounded in the 10 Principles of Economics, group presentations as formative checkpoints, a midterm learning paper, and a final group podcast. Using a convergent mixed-methods design, pre-course and post-course self-assessment surveys measured changes in students' self-perceived economic knowledge and skills across five domains, while thematic analysis of post-course open-ended responses provided qualitative evidence of perspective transformation. Findings indicate a consistent and directionally uniform pattern of upward change across all survey items and all knowledge domains, with the greatest gains concentrated in foundational economic knowledge and the smallest gains observed where students entered with already high levels of competence. Qualitative analysis revealed four themes consistent with Mezirow's (1991) perspective transformation framework: a shift from intuitive to analytical decision-making, from surface to systemic understanding, from personal to social awareness of economic conditions, and from national to global analytical framing. Findings are treated as design inputs for a more methodologically rigorous second cycle and contribute practitioner-generated evidence on the role of authentic assessment ecosystems in fostering knowledge transformation in introductory economics education.